Akaitcho (ca. 1786-1838) - Helm, June; Gillespie, Beryl C. (ARCTIC, 1983)
The Yellowknife Indian leader Akaitcho stepped upon the stage of Canadian history in the afternoon of 30 July 1820 when he met Captain John Franklin and affirmed his willingness to guide and provision Franklin's expedition of exploration "to the shores of the polar sea". . Known in Franklin's time as Copper Indians, the Yellowknives were the northwesternmost division of the widespread Chipewyan peoples. . Ranging broadly in the caribou lands from the East Arm of Great Slave Lake to the Coppermine River, Akaitcho and the Yellowknives traded as meat provisioners into the North West Company post of Fort Providence on the North Arm of Great Slave Lake. For at least a decade the Yellowknives had pillaged furs, stolen women, and occasionally killed Dogrib and Hare Indians, their neighbours to the west and northwest. Dogribs were forced to avoid parts of their traditional hunting range during Akaitcho's years of aggressive leadership. . When, after the terrible overland return from the arctic coast, the starving remnants of the Franklin expedition were rescued by Yellowknives, Akaitcho revealed another facet of his character. Treated with the "utmost tenderness" by their rescuers, Franklin and his party from Fort Enterprise were conveyed to the camp of "our chief and companion Akaitcho." . In consequence of the merger of the North West Company and the Hudson's Bay Company in 1821, the post of Fort Providence had closed in 1823. Akaitcho and the Yellowknives now perforce had to direct their trade into Fort Resolution in company with Chipewyans already attached to that post. (Their intermarriage and absorption into that population brought the eventual disappearance of the Yellowknives as a distinct people.) Driven by vengeance or desperation over killings perpetrated by Yellowknives earlier in the year, in October of 1823 Dogribs attacked the Yellowknife Long Legs and his band, who were encamped in the area between Hottah Lake and Great Bear Lake. Thirty-four Yellowknives perished - four men, thirteen women, and ...